2019
DOI: 10.34208/jba.v20i1.410
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Size, Firm Age, Growth, Audit Reputation, Ownership and Financial Ratio on Intellectual Capital Disclosure

Abstract: The purpose of this research is to examine the effect of size, firm age, growth, audtior reputation, ownership concentration, leverage, market-to-book ratio, liquidity, and profitability on intellectual capital disclosure. This research used 157 non-financial companies that listed in Indonesia Stock Exchange and the data were selected using purposive sampling method during 2012 until 2015. The data were analyzed using multiple regression method. The empirical result show that size, profitability, auditor’s rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
0
0
1
Order By: Relevance
“…The results of this study are in line with researchers (Delvia & Alexander, 2019;Luthan et al, 2018;Novrian et al, 2020) who found that increasing company age affects disclosure of intellectual capital. (A Nugroho, 2012) explains that based on the aging business agency theory, mandatory reporting is more effective.…”
Section: Impact Of Firm Age On Icdsupporting
confidence: 91%
“…The results of this study are in line with researchers (Delvia & Alexander, 2019;Luthan et al, 2018;Novrian et al, 2020) who found that increasing company age affects disclosure of intellectual capital. (A Nugroho, 2012) explains that based on the aging business agency theory, mandatory reporting is more effective.…”
Section: Impact Of Firm Age On Icdsupporting
confidence: 91%
“…Profitabilitas didefinisikan sebagai kemampuan suatu perusahaan dalam menghasilkan laba atas hasil operasi perusahaan pada suatu periode tertentu, yang dihasilkan dari penggunaan aktiva atau modal yang dimiliki perusahaan tersebut (Delvia dan Alexander 2019). perusahaan dengan tingkat profitabilitas yang tinggi mencerminkan kinerja perusahaan yang berjalan dengan baik, dan begitu juga sebaliknya (Almalita 2018).…”
Section: Profitabilitas Dan Manajemen Labaunclassified